Metabolic dysfunction-associated fatty liver disease and implications for cardiovascular risk and disease prevention - Zhou, Xiao-Dong; Cai, Jingjing; Targher, Giovanni; Byrne, Christopher D.; Shapiro, Michael D.; Sung, Ki-Chul; Somers, Virend K.; Chahal, C. Anwar A.; George, Jacob; Chen, Li-Li; Zhou, Yong; Zheng, Ming-Hua (Cardiovascular diabetology, 2022)
The newly proposed term “metabolic dysfunction-associated fatty liver disease” (MAFLD) is replacing the old term “non-alcoholic fatty liver disease” (NAFLD) in many global regions, because it better reflects the pathophysiology and cardiometabolic implications of this common liver disease. The proposed change in terminology from NAFLD to MAFLD is not simply a single-letter change in an acronym, since MAFLD is defined by a set of specific and positive diagnostic criteria. In particular, the MAFLD definition specifically incorporates within the classification recognized cardiovascular risk factors. Although convincing evidence supports a significant association between both NAFLD and MAFLD, with increased risk of CVD morbidity and mortality, neither NAFLD nor MAFLD have received sufficient attention from the Cardiology community. In fact, there is a paucity of scientific guidelines focusing on this common and burdensome liver disease from cardiovascular professional societies. This Perspective article discusses the rationale and clinical relevance for Cardiologists of the newly proposed MAFLD definition.